Developing Qur'an-Based Self-Assessment Instruments for Measuring and Internalizing Religious Character Values - Zainuddin, Zainuddin; Syihabuddin, Syihabuddin; Putra, Aminuddin Prahatama; Nahadi, Nahadi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study aims to develop a valid, practical, and effective self-assessment instrument based on Qur'anic teachings to measure and internalize religious character values. The instrument was designed to evaluate five main aspects: faith, piety, sincerity, righteous deeds, and virtue. Employing a mixed-method approach, the development process included a comprehensive literature review, expert validation, and testing with 71 participants comprising educators and students. Results indicate that the instrument is highly valid (average validation score: 4.5/5), practical (85% usability satisfaction), and effective (88% impact satisfaction). It successfully fosters self-reflection (muhasabah) and enhances the internalization of Qur'anic values such as honesty, patience, and social awareness. The findings underscore the critical role of integrating Qur'anic principles into self-assessment tools to address the challenges of spiritual development in modern education. This instrument offers practical applications for educators at various levels, from schools to higher education, and contributes to the development of character education models rooted in Islamic teachings. Further studies are recommended to explore its application in diverse cultural settings and assess its long-term impact on character building.